Analysis of Regional Industrial Business Potential through the Role of Cash Receipt and Expenditure Accounting System in Supporting Cash Internal Control (Case Study of Municipal Waterworks of Tirtasari Binjai City) - Saharani, Dita; Samri Juliati Nasution, Yenni; Syafina, Laylan (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2024)
This study aims to determine the potential of the regional industrial business through the accounting system for cash receipts and disbursements in supporting internal cash control at Municipal Waterworks of Tirtasari Kota Binjai. The method utilized is descriptive combined with a qualitative approach. The forms of data utilized in this research are primary and secondary, with interview techniques and documentation from the Municipal Waterworks of Tirtasari. One of the industrial businesses that has developed in Binjai City is Municipal Waterworks of Tirtasari, whose role is to provide and distribute clean water to the surrounding community. The accounting system for cash receipts and disbursements at Municipal Waterworks of Tirtasari Kota Binjai is considered to be of good quality, as shown by the research results. The networks that make up the system and related accounting records, along with the functions and documents utilized, are all good in the cash disbursement accounting system. This can be seen from the process of recording accounting in the cash book based on proof of cash out and supporting documents for cash expenditure transactions according to theory. Internal control in this company has not been maximized because the internal checks carried out each year are not carried out suddenly but are still scheduled, as explained in Mulyadi’s theory. This company already uses digital applications for its cash receipts and disbursements accounting system. However, there are still problems that occur in inputting financial data that often experiences errors, this is due to the adjustment of income transferred by the counter and customer relations section, resulting in less support for the level of receipts and disbursements in this company are quite good and issue cash according to necessities only.